Modelando a ocorrência do Jacamim-das-costas-marrons (Psophia dextralis, Psophiidae) na Floresta Nacional do Tapajós - LIMA, Adriana Nascimento (Universidade Federal do Oeste do Pará, 2023)
We estimate the occupancy rate of the bird species Psophia dextralis, the Brown-winged Trumpeter, in the Tapajós National Forest, a protected area located in the state of Pará, Brazil. We used camera traps in four research modules. Ten camera traps were installed per module, which were programmed to take pictures 24/day, remaining 34 days at each point, from July 2019 to January 2020. As predictor variables of occurrence, we collected data for altitude, fruit biomass and forest structure. We used records of detection/non-detection of the species at each site modeled together with the probability of detection. At the end of the monitoring, we had 29 detection events in 20 of the 38 plots, reaching an occupation probability of 0.82 and a detection probability of 0.19 when the species was present. The variables we used did not show significant effects on the occurrence of Psophia dextralis, however, our study presents the first analysis of occupation of the species throughout its distribution. We show that conventional sampling methods can disregard up to 30% of the occurrence of the species whe it is present. In order to make inferences about differences in occupancy rates, we suggest long-term monitoring that considers the average generation time of the species and evaluate the consequences of logging on its populations in the long term.